Produção e pós-colheita de duas cultivares de cebola em função da agua no solo - Vilas Boas, Renato Carvalho; Pereira, Geraldo Magela; De Lima Junior, Joaquim Alves; Oliveira Neto, Cândido Ferreira; Silva, Andre Luiz Pereira [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2016)
This work aimed at assessing the effect of different water tensions in soil on the development and production of two onion cultivars irrigated by drip system. The experiment was carried out in the experimental area of DAG/UFLA, from June to October 2008. The experimental design used was randomized block in factorial scheme 2 × 6, with four repetitions. The treatments comprised two onion cultivars, the hybrid Optima F1 and the non hybrid Alfa Tropical and six water tensions in the soil, i.e., 15, 25, 35, 45, 60 and 75 kPa. The Optima Hybrid F1 presented the best answers regarding the following characteristics: yield of commercial bulbs and average mass of commercial bulbs. The cultivar Alfa showed higher dry matter content and increased mass loss during the post- harvest period. Considering the range studied (15 to 75 kPa) both cultivars should be irrigated when the water pressure in the soil is about 15 kPa at a depth of 0.15 m, in order to obtain more productive plants, larger bulbs and highest average mass of commercial bulbs.
Production and post- harvest of two onion cultivars in function of soil water
Keywords: Allium cepa L; Soil water tension; Trickle irrigation